A low dielectric constant high flexibility glass fiber and a method for preparing the same
Patent Information
- Application Number
- CN202611123078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-28
AI Technical Summary
[0004]综上所述,目前现有的技术方案虽然在一定程度上对玻璃纤维的某些性能进行了改进,但仍存在以下技术问题:介电常数高、柔韧性差
(1)本发明中,低介电复合物采用低温预烧结造粒工艺,通过硼磷铝酸盐低熔点相粘结颗粒,形成疏松多孔结构。该结构具有更高的比表面积与反应活性,可缩短后续高温熔融阶段的均化时间,减少B2O3与磷组分的高温挥发,保证目标组分精确可控。同时硼磷玻璃相可优化玻璃网络结构,协同降低体系的介电常数与介电损耗。
Smart Images

Figure CN122647106B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass fiber technology, specifically to a low dielectric constant, high flexibility glass fiber and its preparation method. Background Technology
[0002] With the rapid development of 5G communication, high-frequency integrated circuits and aerospace, higher requirements have been placed on the dielectric properties, flexibility and mechanical stability of glass fibers used in electronic packaging and substrates. Glass fibers need to have a low dielectric constant to reduce signal transmission loss, excellent flexibility to adapt to complex assembly environments, and chemical stability and mechanical strength during long-term use.
[0003] Currently, mainstream calcium aluminosilicate glass fibers have high dielectric constants, making them unsuitable for high-frequency applications. Existing technologies often introduce large amounts of low-dielectric components such as boron oxide and silicon dioxide to reduce the dielectric constant, but this leads to decreased stability of the glass network structure, a simultaneous decrease in fiber fracture toughness and thermal stability, and a tendency to break during subsequent weaving and composite processing. Existing technology CN119841549A discloses a low-dielectric glass fiber composition, low-dielectric glass fibers, and their preparation method. This technology directly mixes low-dielectric components such as boron oxide into the matrix, resulting in uneven component dispersion, easy agglomeration, and the formation of highly polarized phase regions, leading to poor consistency in dielectric properties. Existing technology CN120383431A discloses a low-dielectric glass fiber material, its preparation method, and applications. This technology improves the dispersibility of cerium oxide by modifying it with sodium stearate, but the reduction in dielectric constant is limited, and it lacks designs to enhance flexibility.
[0004] In summary, although the existing technical solutions have improved some properties of glass fiber to a certain extent, the following technical problems still exist: high dielectric constant and poor flexibility. Summary of the Invention
[0005] In order to solve the above-mentioned problems in the prior art, the present invention provides a low dielectric constant and high flexibility glass fiber and its preparation method, and achieves the following objective: to prepare glass fiber with low dielectric constant and high flexibility.
[0006] To achieve the above objectives, the following technical solution is adopted: A low dielectric constant and high flexibility glass fiber, by weight, comprises the following raw materials: 55-60 parts silicon dioxide, 4-6 parts aluminum oxide, 3-5 parts boron oxide, 2-5 parts magnesium oxide, 4-6 parts zinc oxide, 0.8-1.2 parts zirconium dioxide, 1.2-2 parts modified cerium oxide, 0.5-1.5 parts lithium oxide, 0.5-1 part yttrium oxide, 1-1.2 parts lanthanum oxide, and 18-22 parts low dielectric composite.
[0007] This invention also provides a method for preparing low dielectric constant and high flexibility glass fibers, comprising the following steps: Step 1: Preparation of modified cerium oxide Nano-cerium oxide was dispersed in an ethanol aqueous solution and ultrasonically dispersed for 30-40 min to obtain a suspension. Boric acid, aluminum nitrate, and citric acid were added and stirred until completely dissolved. The pH value was adjusted to 7.5-8 with ammonia. The temperature was then raised to 70-75℃, and the solvent was evaporated under low-speed stirring at 200-300 rpm until a transparent gel was formed. The gel was then aged for 6-8 h. The gel was dried and calcined to obtain modified cerium oxide.
[0008] From the appendix Figure 1 It is evident that the modified cerium oxide particles exhibit a clear core-shell structure, with a uniform outer layer of boron-aluminum composite coating. There is no heavy agglomeration between particles, which effectively improves the dispersibility of nano-cerium oxide and provides a structural basis for its uniform dispersion in glass melt.
[0009] The mass ratio of the nano-cerium oxide, ethanol aqueous solution, boric acid, aluminum nitrate, and citric acid is 100:(1500-1800):(6-9):(13-19):(7-10). The ethanol aqueous solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 7:3.
[0010] The ultrasonic dispersion has a power of 300-400W.
[0011] The drying process involves drying at a temperature of 120-125℃ for 10-12 hours.
[0012] The roasting process involves roasting at a temperature of 750-800℃ for 1-1.5 hours.
[0013] Step 2: Preparation of low-dielectric composite Alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol were mixed evenly and placed in a muffle furnace. Under air atmosphere, the temperature was increased to 300-350℃ at a rate of 1-3℃ / min and held for 0.5-1h; then increased to 800-850℃ at a rate of 4-6℃ / min and held for 1-1.5h. After cooling in the furnace, the mixture was pulverized and passed through a 200-mesh sieve to obtain a low-dielectric composite.
[0014] From the appendix Figure 2 It is evident that the low dielectric complex is an irregular micron-sized aggregate with a rough surface and a loose, porous morphology. This porous structure possesses a higher specific surface area and reactivity.
[0015] The mass ratio of alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol is (5-6):(6-8):(4-5):(2-2.5).
[0016] Step 3: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and a low-dielectric composite are added to a high-speed mixer at 800-1200 rpm and mixed for 30-45 minutes. The mixed material is then placed in a muffle furnace and heated to 800-1000℃ at a rate of 5-10℃ / min, held for 0.5-1 hour, and then heated to 1550-1580℃ at a rate of 5-10℃ / min, held for 3-4 hours to obtain molten glass.
[0017] Step 4: Fiberglass Molding The molten glass is transferred to a spinneret in a drawing furnace, with the spinneret temperature controlled at 1250-1300℃. After flowing out from the small holes in the spinneret, the molten glass is drawn by a high-speed rotating drawing machine to form continuous fibers with a diameter of 10-15 μm. These fibers are then cooled to 90-100℃ using an air-cooling device. Next, the fibers are coated with a sizing agent and dried at 80-120℃ for 1-2 hours to obtain the finished glass fiber product. The sizing agent is an ethanol solution of a silane coupling agent, with a mass fraction of 1-3%. KH550 is selected as the silane coupling agent, and the amount of sizing agent used is 1-2% of the fiber mass.
[0018] The beneficial effects of this invention are as follows: (1) In this invention, the low-dielectric composite is produced by a low-temperature pre-sintering granulation process, in which the particles are bonded by a low-melting-point borophosphorus aluminate phase to form a loose porous structure. This structure has a higher specific surface area and reactivity, which can shorten the homogenization time of the subsequent high-temperature melting stage, reduce the high-temperature volatilization of B2O3 and phosphorus components, and ensure that the target components are precisely controllable. At the same time, the borophosphorus glass phase can optimize the glass network structure and synergistically reduce the dielectric constant and dielectric loss of the system.
[0019] This invention utilizes a sol-gel method to coat nano-CeO2 with a uniform boron-aluminum composite coating layer, significantly improving the wettability of CeO2 particles with silicate melts, inhibiting nanoparticle agglomeration, and ensuring uniform dispersion in molten glass. This uniform dispersion of CeO2 contributes to its auxiliary clarifying effect and enhances the mechanical properties of glass fibers.
[0020] (2) The low dielectric constant and high flexibility glass fiber of the present invention has a low dielectric constant. The prepared glass fiber has a dielectric constant of 3.92-3.98 at 1MHz and a dielectric loss of 0.0020-0.0022 at 1MHz.
[0021] (3) The low dielectric constant and high flexibility glass fiber of the present invention has high flexibility. The tensile strength of the prepared glass fiber product is 2460-2513 MPa and the elongation at break is 3.7-4.0%. Attached Figure Description
[0022] Figure 1 This is a transmission electron microscope (TEM) image of the modified cerium oxide prepared in step one of the present invention.
[0023] Figure 2 This is a scanning electron microscope (SEM) image of the low dielectric composite obtained in step two of this invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0025] Example 1: A low dielectric constant and high flexibility glass fiber and its preparation method A low dielectric constant and high flexibility glass fiber, by weight, comprises the following raw materials: 55 parts silicon dioxide, 6 parts aluminum oxide, 3 parts boron oxide, 5 parts magnesium oxide, 4 parts zinc oxide, 1.2 parts zirconium dioxide, 1.2 parts modified cerium oxide, 1.5 parts lithium oxide, 0.5 parts yttrium oxide, 1.2 parts lanthanum oxide, and 22 parts low dielectric composite.
[0026] A method for preparing low dielectric constant and high flexibility glass fiber includes the following steps: Step 1: Preparation of modified cerium oxide Nano-cerium oxide was dispersed in an ethanol aqueous solution and ultrasonically dispersed for 30 min to obtain a suspension. Boric acid, aluminum nitrate, and citric acid were added and stirred until completely dissolved. The pH value was adjusted to 7.5 with ammonia. The temperature was then raised to 70℃, and the solvent was evaporated under low-speed stirring at 200 rpm until a transparent gel was formed. The gel was then aged for 8 h. The gel was dried and calcined to obtain modified cerium oxide.
[0027] The mass ratio of the nano-cerium oxide, ethanol aqueous solution, boric acid, aluminum nitrate, and citric acid is 100:1500:6:13:7. The ethanol aqueous solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 7:3.
[0028] The ultrasonic dispersion has a power of 400W.
[0029] The drying process involves drying at 120°C for 12 hours.
[0030] The roasting process was carried out at a temperature of 750℃ for 1.5 hours.
[0031] Step 2: Preparation of low-dielectric composite Alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol were mixed evenly and placed in a muffle furnace. Under air atmosphere, the temperature was increased to 300°C at a rate of 1°C / min and held for 1 hour; then increased to 800°C at a rate of 4°C / min and held for 1.5 hours. After cooling in the furnace, the mixture was pulverized through a 200-mesh sieve to obtain a low-dielectric composite.
[0032] The mass ratio of alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol is 5:6:4:2.
[0033] Step 3: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and a low-dielectric composite were added to a high-speed mixer at 800 rpm and mixed for 45 min. The mixed material was then placed in a muffle furnace and heated to 800℃ at a rate of 5℃ / min, held for 1 h, and then heated to 1550℃ at a rate of 5℃ / min, held for 4 h to obtain molten glass.
[0034] Step 4: Fiberglass Molding The molten glass is transferred to a spinneret in a drawing furnace, where the spinneret temperature is controlled at 1250℃. After flowing out from the small holes in the spinneret, the molten glass is drawn by a high-speed rotating drawing machine to form continuous fibers with a diameter of 10-15 μm. These fibers are then cooled to 90℃ using an air-cooling device. Next, the fibers are coated with a sizing agent and dried at 80℃ for 2 hours to obtain the finished glass fiber product. The sizing agent is an ethanol solution of a silane coupling agent, with a mass fraction of 1%. The silane coupling agent used is KH550, and the amount of sizing agent used is 1% of the fiber mass.
[0035] Example 2: A low dielectric constant and high flexibility glass fiber and its preparation method A low dielectric constant and high flexibility glass fiber, by weight, is composed of the following raw materials: 58 parts silicon dioxide, 5 parts aluminum oxide, 4 parts boron oxide, 3 parts magnesium oxide, 5 parts zinc oxide, 1 part zirconium dioxide, 1.8 parts modified cerium oxide, 1 part lithium oxide, 0.7 parts yttrium oxide, 1 part lanthanum oxide, and 20 parts low dielectric composite.
[0036] A method for preparing low dielectric constant and high flexibility glass fiber includes the following steps: Step 1: Preparation of modified cerium oxide Nano-cerium oxide was dispersed in an ethanol aqueous solution and ultrasonically dispersed for 35 min to obtain a suspension. Boric acid, aluminum nitrate, and citric acid were added and stirred until completely dissolved. The pH value was adjusted to 8 with ammonia. The temperature was then raised to 75℃, and the solvent was evaporated under low-speed stirring at 300 rpm until a transparent gel was formed. The gel was then aged for 7 h. The gel was dried and calcined to obtain modified cerium oxide.
[0037] The mass ratio of the nano-cerium oxide, ethanol aqueous solution, boric acid, aluminum nitrate, and citric acid is 100:1700:8:16:8. The ethanol aqueous solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 7:3.
[0038] The ultrasonic dispersion has a power of 400W.
[0039] The drying process was carried out at 125°C for 11 hours.
[0040] The roasting process was carried out at a temperature of 780℃ for 1.5 hours.
[0041] Step 2: Preparation of low-dielectric composite Alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol were mixed evenly and placed in a muffle furnace. Under air atmosphere, the temperature was increased to 330°C at a rate of 2°C / min and held for 1 hour; then increased to 830°C at a rate of 5°C / min and held for 1.5 hours. After cooling in the furnace, the mixture was pulverized through a 200-mesh sieve to obtain a low-dielectric composite.
[0042] The mass ratio of alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol is 5:7:5:2.5.
[0043] Step 3: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and a low-dielectric composite were added to a high-speed mixer at 1000 rpm and mixed for 40 min. The mixed material was then placed in a muffle furnace and heated to 900℃ at a rate of 8℃ / min and held for 1 h. The temperature was then increased to 1570℃ at a rate of 8℃ / min and held for 3.5 h to obtain molten glass.
[0044] Step 4: Fiberglass Molding The molten glass is transferred to a spinneret in a drawing furnace, with the spinneret temperature controlled at 1280℃. After flowing out from the small holes in the spinneret, the molten glass is drawn by a high-speed rotating drawing machine to form continuous fibers with a diameter of 10-15 μm. These fibers are then cooled to 100℃ using an air-cooling device. Next, the fibers are coated with a sizing agent and dried at 100℃ for 1.5 hours to obtain the finished glass fiber product. The sizing agent is an ethanol solution of a silane coupling agent, with a mass fraction of 2%. The silane coupling agent used is KH550, and the amount of sizing agent used is 1.5% of the fiber mass.
[0045] Example 3: A low dielectric constant and high flexibility glass fiber and its preparation method A low dielectric constant and high flexibility glass fiber, by weight, is composed of the following raw materials: 60 parts silicon dioxide, 4 parts aluminum oxide, 5 parts boron oxide, 2 parts magnesium oxide, 6 parts zinc oxide, 0.8 parts zirconium dioxide, 2 parts modified cerium oxide, 0.5 parts lithium oxide, 1 part yttrium oxide, 1 part lanthanum oxide, and 18 parts low dielectric composite.
[0046] A method for preparing low dielectric constant and high flexibility glass fiber includes the following steps: Step 1: Preparation of modified cerium oxide Nano-cerium oxide was dispersed in an ethanol aqueous solution and ultrasonically dispersed for 40 min to obtain a suspension. Boric acid, aluminum nitrate, and citric acid were added and stirred until completely dissolved. The pH value was adjusted to 8 with ammonia. Then the temperature was raised to 75℃ and the solvent was evaporated under low-speed stirring at 300 rpm until a transparent gel was formed. The gel was then aged for 6 h. The gel was dried and calcined to obtain modified cerium oxide.
[0047] The mass ratio of nano-cerium oxide, ethanol aqueous solution, boric acid, aluminum nitrate, and citric acid is 100:1800:9:19:10. The ethanol aqueous solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 7:3.
[0048] The ultrasonic dispersion has a power of 300W.
[0049] The drying process involves drying at 125°C for 10 hours.
[0050] The roasting process was carried out at 800℃ for 1 hour.
[0051] Step 2: Preparation of low-dielectric composite Alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol were mixed evenly and placed in a muffle furnace. Under air atmosphere, the temperature was increased to 350°C at a rate of 3°C / min and held for 0.5 h; then increased to 850°C at a rate of 6°C / min and held for 1 h. After cooling in the furnace, the mixture was pulverized through a 200-mesh sieve to obtain a low-dielectric composite.
[0052] The mass ratio of alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol is 6:8:5:2.5.
[0053] Step 3: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and a low-dielectric composite were added to a high-speed mixer at 1200 rpm and mixed for 30 min. The mixed material was then placed in a muffle furnace and heated to 1000℃ at a rate of 10℃ / min, held for 0.5 h, and then heated to 1580℃ at a rate of 10℃ / min, held for 3 h, to obtain molten glass.
[0054] Step 4: Fiberglass Molding The molten glass is transferred to a spinneret in a drawing furnace, where the spinneret temperature is controlled at 1300℃. After flowing out of the spinneret's small holes, the molten glass is drawn by a high-speed rotating drawing machine to form continuous fibers with a diameter of 10-15 μm. These fibers are then cooled to 100℃ using an air-cooling device. Next, the fibers are coated with a sizing agent and dried at 120℃ for 1 hour to obtain the finished glass fiber product. The sizing agent is an ethanol solution of a silane coupling agent, with a mass fraction of 3%. The silane coupling agent used is KH550, and the amount of sizing agent used is 2% of the fiber mass.
[0055] Comparative Example 1 A type of glass fiber, by weight, comprises the following raw materials: 58 parts silicon dioxide, 5 parts aluminum oxide, 4 parts boron oxide, 3 parts magnesium oxide, 5 parts zinc oxide, 1 part zirconium dioxide, 1.8 parts cerium oxide, 1 part lithium oxide, 0.7 parts yttrium oxide, 1 part lanthanum oxide, and 20 parts low dielectric composite.
[0056] A method for preparing glass fiber includes the following steps: Step 1: Preparation of low-dielectric composite This step is the same as the "Preparation of low dielectric composite" step in Example 2.
[0057] Step 2: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, cerium oxide, and a low-dielectric composite were added to a high-speed mixer at 1000 rpm and mixed for 40 min. The mixed material was then placed in a muffle furnace and heated to 900°C at a rate of 8°C / min, held for 1 h, and then heated to 1570°C at a rate of 8°C / min, held for 3.5 h to obtain molten glass.
[0058] Step 3: Fiberglass Molding This step is the same as the "glass fiber forming" step in Example 2.
[0059] Comparative Example 2 A type of glass fiber, by weight, comprises the following raw materials: 58 parts silicon dioxide, 5 parts aluminum oxide, 4 parts boron oxide, 3 parts magnesium oxide, 5 parts zinc oxide, 1 part zirconium dioxide, 1.8 parts modified cerium oxide, 1 part lithium oxide, 0.7 parts yttrium oxide, 1 part lanthanum oxide, and 20 parts of mixed materials.
[0060] The mixture is obtained by mixing alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol in a mass ratio of 5:7:5:2.5.
[0061] A method for preparing glass fiber includes the following steps: Step 1: Preparation of modified cerium oxide This step is the same as the "Preparation of Modified Cerium Oxide" step in Example 2.
[0062] Step 2: Melting the raw materials Silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and other materials were added to a high-speed mixer at 1000 rpm and mixed for 40 minutes. The mixed materials were then placed in a muffle furnace and heated to 900°C at a rate of 8°C / min, held for 1 hour, and then heated to 1570°C at a rate of 8°C / min, held for 3.5 hours to obtain molten glass.
[0063] Step 3: Fiberglass Molding This step is the same as the "glass fiber forming" step in Example 2.
[0064] Example 4 Performance Testing (a) The dielectric constant and dielectric loss of the glass fiber products prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The glass fiber products were made into glass sheets according to the test method specified in ASTM-D150. The dielectric constant and dielectric loss of the glass fiber at 1MHz were measured using an impedance analyzer. The specific test results are shown in Table 1.
[0065] Table 1 As shown in Table 1, the glass fiber products prepared in Examples 1-3 have a dielectric constant of 3.92-3.98 at 1MHz and a dielectric loss of 0.0020-0.0022 at 1MHz, which proves that the glass fiber prepared by the present invention has a low dielectric constant.
[0066] (ii) Mechanical properties of the glass fiber products prepared in Examples 1-3 and Comparative Examples 1-2 were tested using an electronic universal testing machine to measure the tensile strength and elongation at break of the glass fibers. The specific test results are shown in Table 2.
[0067] Table 2 As shown in Table 2, the tensile strength of the glass fiber products prepared in Examples 1-3 is 2460-2513 MPa and the elongation at break is 3.7-4.0%, which proves that the glass fiber prepared by the present invention has high flexibility.
[0068] Obviously, there are many other possible implementation methods under the concept of this invention. It should be stated here that any changes made under the inventive concept of this invention will fall within the protection scope of this invention.
Claims
1. A method for preparing low dielectric constant and high flexibility glass fiber, characterized in that: The process includes steps such as preparing modified cerium oxide, preparing low-dielectric composites, raw material melting, and glass fiber forming. The preparation of modified cerium oxide involves dispersing nano-cerium oxide in an aqueous ethanol solution, ultrasonically dispersing it to obtain a suspension, adding boric acid, aluminum nitrate, and citric acid, stirring until dissolved, and adjusting the pH value. Then, the temperature is raised, the solvent is stirred and evaporated to form a transparent gel, and aging continues; the gel is dried and calcined to obtain modified cerium oxide; the mass ratio of nano-cerium oxide, ethanol aqueous solution, boric acid, aluminum nitrate and citric acid is 100:(1500-1800):(6-9):(13-19):(7-10); the calcination temperature is 750-800℃ and the calcination time is 1-1.5h; The preparation of the low-dielectric composite involves uniformly mixing alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol, and then gradually heating and holding the mixture in air. After furnace cooling, the mixture is pulverized and sieved to obtain the low-dielectric composite. The mass ratio of alumina, boron oxide, aluminum dihydrogen phosphate, and polyvinyl alcohol is (5-6):(6-8):(4-5):(2-2.5). The gradual heating and holding process involves first heating to 300-350℃ at a rate of 1-3℃ / min and holding for 0.5-1h; then heating to 800-850℃ at a rate of 4-6℃ / min and holding for 1-1.5h. The raw material melting process involves uniformly mixing silica, magnesium oxide, aluminum oxide, boron oxide, zinc oxide, zirconium dioxide, lithium oxide, yttrium oxide, lanthanum oxide, modified cerium oxide, and a low-dielectric composite; then placing the mixture in a muffle furnace and melting it through a gradient heating process to obtain molten glass. The weight ratio of the raw materials used is as follows: silica 55-60 parts, aluminum oxide 4-6 parts, boron oxide 3-5 parts, magnesium oxide 2-5 parts, zinc oxide 4-6 parts, zirconium dioxide 0.8-1.2 parts, modified cerium oxide 1.2-2 parts, lithium oxide 0.5-1.5 parts, yttrium oxide 0.5-1 part, lanthanum oxide 1-1.2 parts, and low-dielectric composite 18-22 parts. The glass fiber forming process involves transferring molten glass to a drawing furnace for drawing, cooling it, coating the fibers with a sizing agent, and drying it to obtain the finished glass fiber product.
2. The method for preparing low dielectric constant and high flexibility glass fiber according to claim 1, characterized in that: The pH value is adjusted in the step of preparing modified cerium oxide by using ammonia water to adjust the pH value to 7.5-8.
3. The method for preparing low dielectric constant and high flexibility glass fiber according to claim 1, characterized in that: The gradient heating melting in the raw material melting step is as follows: first, the temperature is increased to 800-1000℃ at a rate of 5-10℃ / min and held for 0.5-1h; then, the temperature is increased to 1550-1580℃ at a rate of 5-10℃ / min and held for 3-4h.
4. The method for preparing low dielectric constant and high flexibility glass fiber according to claim 1, characterized in that: The impregnating agent in the glass fiber forming step is an ethanol solution of silane coupling agent, with a mass fraction of 1-3%, and KH550 is selected as the silane coupling agent.
5. The method for preparing a low dielectric constant and high flexibility glass fiber according to claim 1, characterized in that: In the glass fiber forming step, the amount of sizing agent used is 1-2% of the fiber mass.
Citation Information
Patent Citations
Low-dielectric glass fiber composition, low-dielectric glass fiber and preparation method of low-dielectric glass fiber
CN119841549A
Glass fibre with low dielectric constant
CN101269915A
Low-dielectric glass fiber material as well as preparation method and application thereof
CN120383431A